Model Pembelajaran Inquiry Learning dengan Media Quizizz untuk Meningkatkan Berfikir Kritis Siswa - Hendrik Pratama; Tri Mei Mantalia (Lembaga Bale Literasi, 2023)
This study aims to increase IPAS learning interest in students who are still low, because IPAS learning is a subject that is considered quite difficult for students. This is what encourages researchers to develop creativity in learning. Learning media can be used to make students interested in learning. the media used by researchers is the quizizz application. This study aims to see the effect of the quizizz application on the interest in learning IPAS of class X students of SMKN 2 Bagor. This research is quantitative research using Inquiry Learning learning media to improve students' critical thinking skills. Data collection techniques in research by conducting observations and tests. This test technique is done using a test test using the Quizizz application in the form of multiple choice. The research was conducted with 31 students in class X Culinary 2 SMKN 2 Bagor. The results obtained in this study were an increase in students' critical thinking skills from the pre-cycle stage, 35.29% of 11 students for the first cycle stage obtained 51.6% of 16 students, and at the second cycle stage amounted to 80.6%. This study proves that the application of the Inquiry Learning model using the Quizizz Application can improve students' critical thinking skills.